Sistem Pendukung Keputusan Pemberian Nilai Pada Asisten Pratikum Jurusan Teknik Informatika Dengan Metode Simple Additive Weighting (Saw) Berbasis Web 2.0 - Liyando Hermawan Hasibuan; Achmad Arif Munaji; Agatha Deolika; Nadya Chitayae; Erik Setiawan (Journal of Information Technology, 2022)
Abstract— In this modern era, the assessment of an individual with other individuals is still in the subjective stage, a human being assesses the abilities of other humans by using various points of view. Likewise, what Pratikan did to his Pratikum Assistants gave them an assessment that was in accordance with what they had, but the assessment sometimes had different parameters so that the conclusions between one person and another were different, there was no similarity in judging one person. With the Simple Additive Weighting (SAW) method, the problem can be solved with the help of this method. Websites that have become part of social life and are closely integrated in daily activities. So using the SAW method, one of the alternatives in the assessment can provide a Pratikum Assistant. The results obtained from these values ​​can provide a new perspective on various kinds of problems. Deciding that no Practicum Assistant can be reused or the results of a given Assessor can help create a new resolution to the pattern of scoring in Practicum Assistants.